Relationships between temperament, meat quality, and carcass traits in Nellore cattle - Sant'Anna, Aline Cristina (2019)
The aim of this study was to evaluate the relationship between temperament in Nellore bulls with carcass and meat quality traits. In total, 1,400 bulls were studied, and temperament was assessed using two measurements: movement score (MOV) and flight speed test (FS). Both MOV and FS were measured at two time points, with background (MOV and FS) temperament measured at yearling age, -550 d after birth, and the preslaughter (MOVI and FS) temperament measured at the end of the feedlot period. The change of temperament resulting in an increase or decrease in reactivity was also used to measure meat quality. The traits used to define carcass and meat quality included carcass bruises (BRU), hot carcass weight (HCW, kg), ribeye area (REA, cm), backfat thickness (BFT, cm), marbling score (MS), meat pH after thawing (pH), presence or absence of dark cutters, color parameters of luminosity (L*), redness (a') and yellowness (b*), cooking loss (CL, %), and Warner-Bratzler shear force (WBSF, kg). A principal component (PC) analysis was initially applied to the carcass and meat quality traits, followed by logistic regression models and linear mixed models to evaluate the effects of temperament on carcass and meat quality. The risks of carcass bruises and dark cutters did not differ as a function of any temperament trait (P > 0.05). In turn, animals classified as high MOV, (reactive) had lower PC3 values (P = 0.05), CL (P = 0.02), and tended to have lower MS (P = 0.08). In addition, animals classified as high FSb (faster and reactive cattle) produced carcasses with smaller REA (P < 0.01), higher meat pH (P < 0.01), lower color gradients (L*, P = 0.04; b*, P < 0.01), and lower PC1 and PC4 scores (P < 0.01) when compared with the low FS class. For preslaughter temperament, high MOV was related to lower color a' (P = 0.04), whereas high FS s was related to lower HCW, MS, and PC2 (P < 0.01) than the calmer ones (low FSp,). The reduction in MOV was related to more tender meat, and the reduction in FS to heavier carcass and brighter meat. We conclude that excitable temperament in Nellore cattle may have negative effects in some of the carcass and meat quality attributes assessed, mainly those related to muscle deposition on carcass and color gradients. Measurement of temperament before the cattle entered the feedlot was a better predictor of carcass and meat quality traits, compared with temperament assessment at the end of the feeding period.